GEODYNAMICS, MAGMATISM, AND DEGASSING OF THE EARTH - Azbel I.Y.; Tolstikhin I.N. (My University, 1990)
In this study terrestrial degassing processes are identified, formalized both on local and global scales, and combined in a single model of evolution of the upper mantle (which constitutes of the silicate Earth), the crust, and the atmosphere; unknown parameters of these processes are estimated by means of numerical modelling. The model envisages: early intensive convection and fractionation in the upper mantle resulting in sharp degassing of its matter; later, relatively slow convection in this reservoir, accompanied by partial melting of silicate matter in rift and subduction zones; uplift of melts into the oceanic and continental crust and their degassing; early formation and subsequent recycling of the continental crust and its degassing due to intracrustal magmatism and metamorphism; and accumulation of gases (excepting He) in the atmosphere.